Assessing Water Stress in Punjab Through the Water Poverty Index: A Spatiotemporal Analysis - Kaur, Harpreet; Vatta, Kamal; Priscilla, Laishram (Annals of Arid Zone, 2025)
This paper examines the status of water stress and its pattern while identifying key areas for intervention to address the water scarcity challenges in Punjab, India. This study employed a micro-level approach to construct the modified water poverty index (MWPI) by using National Sample Survey (NSS) data from the 69th and 76th rounds. The key findings of the spatiotemporal analysis revealed that the state’s overall water poverty status has deteriorated from 0.69 in 2012 to 0.66 in 2018. Descriptive data analysis highlights that deterioration in the index value of access, capacity, and environmental components is a matter of concern. Furthermore, the sub-component evidence reveals that dwindling access to safe water, longer collection times and distances, a growing burden of waterborne diseases, and the stagnant water surrounding drinking water sources due to inadequate water infrastructure highlight critical areas where the government needs to intervene with target policy initiatives that urgently and explicitly address these challenges and ensure the sustainable water resource management.